Final Journey : the Fate of the Jews in Nazi Europe. - Gilbert, Martin (RosettaBooks, 2015)
A thoughtful and rigorous examination of the Jewish experience under Hitler's "Final Solution"'based on eyewitness accounts and contemporary evidence. Focusing on firsthand narratives from survivors and supported by contextual scholarship, Gilbert presents a masterful cross-section of the experiences of the millions of European Jews who lost their homes, careers, families, and lives at the hands of Hitler's "Final Solution." The accounts of these journeys are at once unique and unified by both their tragedy and by their triumphs. Gilbert's vast knowledge on the subject, coupled with his frank and readable style, makes Final Journey accessible to readers and scholars alike. The text is supported by eighty-four photographs'many of which were published for the first time in 1979'and twenty-four pages of maps prepared by the author, which help bring the stories of the men, women, and children back to life in unflinching detail